Desensitisasi Sistematis: Upaya Kuratif untuk Meningkatkan Kepercayaan Diri Seorang Konseli Penderita Glossophobia - Syaifatul Jannah; Siti Azhara; Moh. Wardi (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2022)
Abstract: This article is about behavior counseling with systematic desensitization techniques to increase confidence of a female student with glossophobia, which is described in two focuses, that is, how is the behavior counseling process with systematic desensitization techniques to increase confidence of a female student with glossophobia and what is the final result of behavior counseling with systematic desensitization technique to increase confidence in a female student with glossophobia. The research method uses a qualitative approach, with the type of case study, and the data collection methods used are interviews, observations, and documentations. The results of data collection were processed using data analysis techniques from Milles and Huberman, those are data reduction, data display, and conclusion. The subject in this study is a student who suffers from glossophobia. The results showed that there were five stages of counseling used, those are problem identification, diagnosis, prognosis, treatment, and evaluation and follow-up. In giving treatment, the researcher applied a systematic desensitization technique which was carried out for five meetings with the steps. First, developing a hierarchy of anxiety. Second, deal with the hierarchy of anxiety from the mildest to the most severe. Third, do relaxation. Fourth, conditioning. Fifth, conduct self-regulated learning. Sixth, give homework. Seventh, fill out a reflection questionnaire. While the final result of the implementation of counseling, which can be said to be successful, because the anxiety experienced by the counselee begins to decrease and looks more confidentAbstrak: Artikel ini tentang konseling behavior dengan teknik desensitisasi sistematis untuk meningkatkan kepercayaan diri seorang mahasiswi penderita glossophobia, yang dijabarkan dalam dua fokus yaitu, bagaimana proses konseling behavior dengan teknik desensitisasi sistematis untuk meningkatkan kepercayaan diri seorang mahasiswi penderita glossophobia dan bagaimana hasil akhir konseling behavior dengan teknik desensitisasi sistematis untuk meningkatkan kepercayaan diri seorang mahasiswi penderita glossophobia. Adapun metode penelitian ini menggunakan pendekatan kualitatif, dengan jenis studi kasus, dan metode pengumpulan data yang dipakai adalah wawancara, observasi, serta dokumentasi. Hasil pengumpulan data kemudian diolah dengan menggunakan teknik analisis data dari Milles dan Huberman, yakni reduksi data, display data, dan conclusion. Subjek dalam penelitian ini yaitu seorang mahasiswi yang menderita glossophobia. Adapun hasil penelitian menunjukkan bahwa terdapat lima tahapan konseling yang digunakan yaitu identifikasi masalah, diagnosis, prognosis, treatment, dan evaluasi dan follow up. Dalam pemberian treatment peneliti menerapkan teknik desentisisasi sistematis yang dilakukan selama lima kali pertemuan dengan langkah-langkah, pertama, menyusun hierarki kecemasan. Kedua, menangani hierarki kecemasan dari yang paling ringan ke yang paling berat. Ketiga, melakukan relaksasi. Keempat, pengkondisian. Kelima, melakukan self regulated learning. Keenam, memberikan tugas rumah. Ketujuh, mengisi angket refleksi. Sedangkan hasil akhir dari pelaksanaan konseling, yaitu dapat dikatakan berhasil, karena kecemasan berbicara di depab public yang dialami oleh konseli mulai menurun dan terlihat lebih percaya diri